Zoom radiograph revision course 2026: celebrating 12 years of training future radiologist - Kaur, Arlinder; Mumin, Nazimah; Abdul Kadir, Roqiah Fatmawati; Razalli, Mazuin; Arifin, Natasha; Peter, Alan Basil; Subramaniam, Mahalatchumi; Nasran, Natasha (Faculty of Medicine, 2025)
The 12th zoom radiograph revision course was held on 2 august 2025 at UiTM Selayang Campus. For over a decade, it has been the go-to preparatory course for part 2 candidates in the master of radiology and parallel pathway programs.